1993
DOI: 10.1172/jci116380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of excess alpha-hemoglobin chains on cellular and membrane oxidation in model beta-thalassemic erythrocytes.

Abstract: While red cells from individuals with ,8 thalassemias are characterized by evidence of elevated in vivo oxidation, it has not been possible to directly examine the relationship between excess a-hemoglobin chains and the observed oxidant damage. To investigate the oxidative effects of unpaired a-hemoglobin chains, purified a-hemoglobin chains were entrapped within normal erythrocytes. These "model" ,8-thalassemic cells generated significantly (P < 0.001 ) greater amounts of methemoglobin and intracellular hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
1
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(136 citation statements)
references
References 42 publications
4
128
1
3
Order By: Relevance
“…However, over time the damage becomes more apparent. Indeed, the oxidant and challenge dosage (50 mM PMS) used in this study was specifically chosen as previous studies have demonstrated that the oxidant treated RBC exhibited similar characteristics to sickle and thalassemic cells [15,17,24]. In support of this finding, the PMS-treated murine cells demonstrated very similar in vivo circulation to that of model ß thalassemia murine RBC [3,17,49].…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…However, over time the damage becomes more apparent. Indeed, the oxidant and challenge dosage (50 mM PMS) used in this study was specifically chosen as previous studies have demonstrated that the oxidant treated RBC exhibited similar characteristics to sickle and thalassemic cells [15,17,24]. In support of this finding, the PMS-treated murine cells demonstrated very similar in vivo circulation to that of model ß thalassemia murine RBC [3,17,49].…”
Section: Discussionmentioning
confidence: 53%
“…Survival of fluorescently labeled control and PMS-oxidized RBC was monitored by analyzing the percent of fluorescently labeled RBC by flow cytometry (FACSCalibur Flow Cytometer, BD Biosciences, San Jose, CA) [45,46]. To better correlate PMS-treatment with a known hematological abnormality, model murine ß thalassemic cells were prepared via osmotic lysis and resealing as previously described [3,17,48,49]. Model ß thalassemic murine RBC are produced via the entrapment of purified human alpha-hemoglobin chains within normal murine RBC.…”
Section: Murine Transfusion Modelmentioning
confidence: 99%
See 3 more Smart Citations